Bridging the gap between social and market rented housing in six European countries? - Haffner (IOS Press, 2013)
The once clear demarcation of funding and roles of the social and market rental sectors seems to have become blurred in a number of European countries. Social renting is no longer provided only by non-profit organisations. The central issue in this book is the extent to which a gap can be identified between the social and market rental sectors in six countries in north-west Europe (England, Belgium, France, Germany, Ireland and the Netherlands). The gap depends on similarities and differences between the two rental sectors. From an empirical viewpoint it conveys who provides what in rental housing, the government policies that are relevant and the outcomes that are achieved. From a theoretical point of view the gap is about the extent to which accommodation in the two sectors can be considere